Timing of onset of symptom for COVID-19 from publicly reported confirmed cases in Uganda - Ario, Alex Riolexus (Pan Afr Med J, 2021)
INTRODUCTION: incubation period for COVID-19, 2-14 (average 5-6) days. Timing of onset of COVID-19 signs and symptoms amongst cases in Uganda is however not known. METHODS: we utilized data on real-time reverse transcription polymerase chain reaction (RT-PCR) confirmed cases to investigate symptom onset timing, from 21(st) March to 4(th) September 2020. Since timing of COVID-19 symptom onset is highly likely to be an interval rather than a point estimate, we generated 3-tertile categories: 1(st), 2(nd) and 3(rd) tertile denoting symptom presentation within 3, 4 to 6 and at least 7 days. We considered all signs and symptoms in the database and analysed using Chi-square test and multinomial logistic regression, controlling for age and sex. RESULTS: we analysed a total of 420 symptomatic case-patients; 72.0% were males, median age of 33 years. Common symptoms were cough (47.6%), running nose (46.2%), fever (27.4%), headache (26.4%) and sore throat (20.5%). We utilized 293 cases with clinical symptom onset date recorded. Most of the patients, 37.5%, presented symptom within 3 days, 31.4% had symptoms in the 2(nd) and 31.4% in 3(rd) tertile, denoting 4 to 6 days and at least 7 days after exposure. Running nose (RRR=0.45, 95%CI: 0.24-0.84) and chest pain (RRR=0.64, 95%CI: 0.09-0.72) were more likely to occur in 3(rd) tertile than 1(st) or 2(nd) tertile. Cases aged ≥20 years were less likely to have symptoms in the 1(st) and 2(nd) tertile compared to ≤20 years (p<0.05). CONCLUSION: our study provides empirical evidence for epidemiological characterization of cases by signs and symptoms which complements current proposals for the length of active monitoring of persons exposed to SARS-CoV-2.